2014
DOI: 10.1186/1471-2458-14-418
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis treatment discontinuation and symptom persistence: an observational study of Bihar, India’s public care system covering >100,000,000 inhabitants

Abstract: BackgroundThe effectiveness of India’s TB control programs depend critically on patients completing appropriate treatment. Discontinuing treatment prior to completion can leave patients infectious and symptomatic. Developing strategies to reduce early discontinuation requires characterizing its patterns and their link to symptom persistence.MethodsThe 2011 BEST-TB survey (360 clusters, 11 districts) sampled patients (n = 1007) from Bihar’s public healthcare system who had initiated treatment >6 months prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…In a framework where providers with higher knowledge could charge higher fees, one possible explanation for our finding that knowledge is not adequately priced could be due to substantial asymmetric information: patients cannot directly assess providers' knowledge and cannot infer it from outcomes (either theirs or of other patients) due to variations in case-mix and infrequent experience. However, another explanation might be that knowledge might be only very loosely related to performance, 13 which is what ultimately matters for the patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a framework where providers with higher knowledge could charge higher fees, one possible explanation for our finding that knowledge is not adequately priced could be due to substantial asymmetric information: patients cannot directly assess providers' knowledge and cannot infer it from outcomes (either theirs or of other patients) due to variations in case-mix and infrequent experience. However, another explanation might be that knowledge might be only very loosely related to performance, 13 which is what ultimately matters for the patient.…”
Section: Resultsmentioning
confidence: 99%
“… 12 Previous studies of rural patients in Bihar treated for TB using DOTS (Directly Observed Treatment, Short course) in the public sector show high rates of drop-out and symptom persistence, despite completing treatment. 13 Another study that sampled 371 174 individuals in 30 districts across India shows that nearly half of those with TB who sought care did so in private sector and non-DOTS settings. 14 Yet, the potential for higher quality TB diagnosis and treatment as represented by the limits of provider knowledge remains ill characterised in settings like Bihar, especially among private sector providers who are the first point of medical contact for most rural patients.…”
Section: Introductionmentioning
confidence: 99%
“…had other TB therapy within a month of starting BDQ in study C209, exhibited slower clearance of the bacteria. One possible explanation is that after receiving some TB therapy, multiplying bacteria are already cleared whereas nonmultiplying bacteria or persisters remain, being then more difficult to clear from the body . Other possible explanations are bias from patient selection, different effectiveness of the background TB regimen, or a multiphasic mechanism of bacterial clearance not captured by the model.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, factors significantly associated with this group were patient's age, educational status, wealth index and type of health services from where treatment was sought for other illnesses. Other studies too have reported age, illiteracy, and poor socioeconomic status as risk factors for default . There is a need to focus on this high‐risk group with enhanced counselling and follow‐up services to retain them in the treatment network.…”
Section: Discussionmentioning
confidence: 99%